"It just fits my needs better": Autistic students and parents' experiences of learning from home during the early phase of the COVID-19 pandemic. (November 2021) - Heyworth, Melanie; Brett, Simon; Houting, Jacquiline den; Magiati, Iliana; Steward, Robyn; Urbanowicz, Anna; Stears, Marc; Pellicano, Elizabeth
Background and aims: The COVID-19 pandemic has caused unprecedented disruption to people's lives, especially for families, whose children have been taken out of schools during lockdown restrictions and required to learn from home. Little is known, however, about the perceived impact of the lockdown restrictions on the educational experiences of autistic children and young people – a group whose conventional schooling experiences are already often challenging. In this study, we sought to (1) understand these experiences from the perspectives of autistic young people and their parents, and (2) identify the underlying sources of positive experiences at this challenging time, in order to inform the ways in which autistic children might flourish at school in more normal times. Methods: Ninety-one Australian participants, including 16 autistic young people aged 12–18 years, 32 autistic parents and 43 non-autistic parents of autistic young people aged 3–18 years, took part in semi-structured interviews about their experiences of life during the initial phase of the COVID-19 pandemic. The interviews were subjected to reflexive, thematic analysis to identify themes and subthemes for each research question. Results: Overall, our participants initially found the transition to learning from home extremely challenging, with parents reporting that the support received from schools was far from adequate. After that initial period of transition, however, many autistic children reported flourishing at home both educationally and personally. For these children and families, we identified three key ingredients essential to this flourishing, including: (i) the importance of connected, trusting relationships ('people'); (ii) the sensory and social safety of home ('place'); and (iii) the flexibility to pace and structure learning to suit the individual child ('time'). Conclusions: While the initial COVID-19 lockdown presented many challenges to children learning at home, there were aspects of this otherwise-unsettling situation that enabled children to thrive and from which we can learn for the future. Implications: These findings have important implications for understanding how and when autistic children might thrive in institutional educational settings once the pandemic subsides, focusing on the relationships between teachers and students, the nature of the physical learning environment and the need for greater flexibility in planning the school day.